1975
DOI: 10.1148/115.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Nephrosis Induced by Water-Soluble Triiodinated Contrast Media in Man

Abstract: Renal biopsies were performed in 211 patients which 10 days of excretory urography or renal arteriogrpahy in which diatrizoate, iothalamate or ioxithalamate had been used. In 47 renal specimens, osmotic nephrosis of the proximal tubular cells was found. Previous renal function had been normal in 10 patients, moderately impaired in 19, and severely impaired in 18. Tubular atrophy and/or necrosis was associated with histological features in 29 of 47 patients. Diffuse osmotic nephrosis was more often found in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

1977
1977
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(24 citation statements)
references
References 12 publications
1
21
0
2
Order By: Relevance
“…These enyzmatic findings are parallel to the histologi cal studies, which have shown structural changes in the proximal tubular cells [8,15,16], However, the interpre tation of the enzymatic and morphologic alterations has remained unclear, and the correlation of such results to renal function has not been definitely demonstrated [17], Furthermore, categorical confirmation of CM-associated nephrotoxicity is still lacking.…”
Section: Introductionmentioning
confidence: 57%
“…These enyzmatic findings are parallel to the histologi cal studies, which have shown structural changes in the proximal tubular cells [8,15,16], However, the interpre tation of the enzymatic and morphologic alterations has remained unclear, and the correlation of such results to renal function has not been definitely demonstrated [17], Furthermore, categorical confirmation of CM-associated nephrotoxicity is still lacking.…”
Section: Introductionmentioning
confidence: 57%
“…The most significant characteristic of this phenomenon includes a focal or diffuse vacuolization of the proximal tubule or even tubular necrosis. In an early study conducted by Moreau et al [49 ]on 211 patients who underwent renal biopsy within 10 days of the angiographic procedure, there were 47 cases of osmotic nephrosis and contemporary tubular atrophy or necrosis in 29 patients. Osmotic nephrosis often develops in patients with severe baseline impairment of renal function.…”
Section: Pathophysiology Of Contrast-induced Nephropathymentioning
confidence: 99%
“…Moreau et al (42) described vacuolization in the proximal convoluted tubules as one of the first structural changes in nephrotoxicity. A subsequent experiment by Tervahartiala et al (43) that compared morphologic changes in rat kidneys after injection of high-, low-, and iso-osmolar iodinated contrast agents with Magnevist showed clear vacuolization within two hours of any iodinated contrast treatment, but no vacuolization up to 48 hours after Magnevist.…”
Section: Nephrotoxicitymentioning
confidence: 99%